2006
DOI: 10.1529/biophysj.106.082735
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Tightly Membrane-Bound Mastoparan-X, a G-Protein-Activating Peptide, Determined by Solid-State NMR

Abstract: The structure of mastoparan-X (MP-X), a G-protein activating peptide from wasp venom, in the state tightly bound to anionic phospholipid bilayers was determined by solid-state NMR spectroscopy. Carbon-13 and nitrogen-15 NMR signals of uniformly labeled MP-X were completely assigned by multidimensional intraresidue C-C, N-CalphaCbeta, and N-Calpha-C', and interresidue Calpha-CalphaCbeta, N-CalphaCbeta, and N-C'-Calpha correlation experiments. The backbone torsion angles were predicted from the chemical shifts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 51 publications
6
99
0
Order By: Relevance
“…A typical 31 P 90°-pulse length of 3.5 μs was used. 31 P chemical shift spectra were obtained using a spin echo sequence (90°-τ-180°-τ-acquire with τ=9 μs), 65 kHz RF field for TPPM decoupling of protons, and a recycle delay of 3 seconds. A typical spectrum required the co-addition of about 100 scans for aligned samples and about 1,000 transients for MLVs.…”
Section: Solid-state Nmrmentioning
confidence: 99%
See 2 more Smart Citations
“…A typical 31 P 90°-pulse length of 3.5 μs was used. 31 P chemical shift spectra were obtained using a spin echo sequence (90°-τ-180°-τ-acquire with τ=9 μs), 65 kHz RF field for TPPM decoupling of protons, and a recycle delay of 3 seconds. A typical spectrum required the co-addition of about 100 scans for aligned samples and about 1,000 transients for MLVs.…”
Section: Solid-state Nmrmentioning
confidence: 99%
“…Since the use of a high RF power in the PISEMA experiment could dehydrate the bilayer sample, cold air was circulated in the probe to reduce the effect of RF heat on the sample. In addition, the quality of aligned samples was examined using 1D 31 P experiments before and after PISEMA experiments. Data processing was accomplished using the Spinsight software (Varian) on a Sun Sparc workstation.…”
Section: Solid-state Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…This clear difference in zoospore behavior and responses toward 1 and 2 in an aqueous solution of 10 also supports our tentative conclusion that the receptors of 1 and 2 are different, and these distinguishable sensing systems respectively play an important role in the events of host recognition and consequent infection of root tissues of the host plants. Islam et al 27) suggested that an important intracellular signaling cascade involved in the host-recognition system is likely to be mediated by cAMP, simply because treatment of the swimming zoospores with a G-protein activator, mastoparan, 28) led to their encystment followed by spore germination. Although it is simplistic thinking, we examined the effects of the adenylate cyclase activator forskolin (11) 18) and the adenylate cyclase …”
Section: Effects Of Some Purine Derivatives and Chemical Reagents Assmentioning
confidence: 99%
“…10 It is one of a family of peptides that directly activate G proteins in a similar fashion to other G-protein coupled receptors. 11 Mastoparan-X is only partially folded in water, but it folds into an amphipathic helix when bound to membranes 12,13 or bound to the G protein a-subunit. 14 In both cases, the helix extends from residue 3 to residue 14 of the peptide.…”
Section: Introductionmentioning
confidence: 99%